Health related quality of life regarding to gender in sarcoidosis - Dudvarski-Ilić, Aleksandra (Array, 2009)
Abstract: Evaluation of the health-related quality of life (HRQoL) in patients with respiratory diseases has been increasingly included into regular clinical studies, and HRQL in sarcoidosis has been evaluated since not a long ago. The aim of the study was to evaluate HRQoL in patients with sarcoidosis regarding gender differences, pre and after therapy. We investigated 202 pathohistologically verified sarcoidosis patients (154 female and 48 male) without comorbidities. HRQL was assessed by the disease-specific Sarcoidosis Health Questionnaire (SHQ), which contains 29 items, and cover three domains: everyday functioning, physical activities and emotional state. Total score, as well as the scores for each SHQ domains were calculated. HRQoL was estimated pre and after three months of therapy. At the study start, the lowest score value for the whole group was reported in SHQ emotional state domain (4.24), and the highest in domain of physical functioning (4.7). After three months, the lowest values were reported in domain of everyday activities, while the highest scores were found in emotional domain; all SHQ scores increased, but reached the statistical significance only in the everyday functioning and the physical activities domains. Analyzing mean SHQ scores in male and female sarcoidosis pts before therapy we found high statistically lower emotional and total score in female pts, as well as lower physical score. After the three months therapy we found high statistical difference in physical domain (i.e.women had lower physical score than men). Female sarcoidosis pts showed lower emotional, physical and total score before therapy. After the three-month therapy we found that women had lower physical score than men. SHQ showed good measurement properties both in the cross-sectional and longitudinal assessment of sarcoidosis patients